Sulfation Pattern Dependent Iron(III) Mediated Interleukin‐8 Glycan Binding. (9th December 2021) - Brunori, Francesco; Padhi, Deepak Kumar; Alshanski, Israel; Freyse, Joanna; Dürig, Jan‐Niklas; Penk, Anja; Vaccaro, Luigi; Hurevich, Mattan; Rademann, Jörg; Yitzchaik, Shlomo
Abstract: Cytokines such as interleukin‐8 activate the immune system during infection and interact with sulfated glycosaminoglycans with specific sulfation patterns. In some cases, these interactions are mediated by metal ion binding which can be used to tune surface‐based glycan‐protein interactions. We evaluated the effect of both hyaluronan sulfation degree and Fe 3+ on interleukin‐8 binding by electrochemical impedance spectroscopy and surface characterizations. Our results show that sulfation degree and metal ion interactions have a synergistic effect in tuning the electrochemical response of the glycated surfaces to the cytokine. Abstract : The synergistic effect of hyaluronan sulfation degree and metal ion on interleukin‐8 binding was investigated by electrochemical impedance spectroscopy and surface characterizations.